CHIP away at the marrow-clot connection: inflammation, clonal hematopoiesis, and thromboembolic disease - Angela Todorovski; Tzu-Fei Wang; Marc Carrier; Yan Xu (Blood Advances)
Abstract: Both the incidence and prognosis of arterial atherothrombosis and venous thromboembolism are strongly correlated with increasing age. Over the past decade, clonal hematopoiesis of indeterminate potential (CHIP) has been identified as a novel biomarker for cardiovascular disease. Driven by somatic mutations in the hematopoietic system, the epidemiology of CHIP is highly age dependent: among individuals aged ≥70 years in the general population, estimated prevalence of CHIP exceeds 10%. Several additional risk factors for CHIP have emerged in recent years, including smoking, receipt of anticancer therapy, and germ line predispositions. CHIP carriers consistently have higher risk of incident arterial atherothrombosis, even after accounting for traditional cardiovascular risk factors. However, the magnitude of this association varies across studies. In addition, individuals with established cardiovascular disease and CHIP have higher risks of recurrence and all-cause mortality than their non-CHIP counterparts. An association between CHIP carriership and incident venous thromboembolism has recently been made, although additional studies are needed to confirm this finding. No approved therapy exists to modify the cardiovascular risk among CHIP carriers. However, canakinumab showed promise in a post-hoc analyses of patients with TET2-mutated CHIP, and other anti-inflammasome agents are actively under development or evaluation. In this review, we provide an overview of CHIP as a mediator of thromboembolic diseases and discuss emerging therapeutics aimed at intervening on this thrombo-inflammatory nexus.